Yield of corn grown after green manures under no-tillage and conventional management system - Carvalho, MAC de; Soratto, R. P.; Athayde, MLF; Arf, O.; Sa, M. E. de (Empresa Brasil Pesq Agropec, 2004)
The succession of grain crops after green manures can improve physical, chemical and biological soil conditions, with increases on grain yield. The objective of the study was to evaluate the agronomical characteristics and the yield of corn grown after green manures under no-tillage and conventional tillage (one disc harrow and two levelling harrow) systems. The experiment was carried out in a Typic Haplustox, covered by savanna vegetation, in Selviria, MS, Brazil. The experimental design used was randomized blocks, in a split plot scheme, with four replications. Four green manures were used: black velvet bean, pigeon pea, sunn hemp and millet and fallow area (spontaneous vegetation). The sunn hemp previously grown in spring increased 18.5% the corn yield, compared to the fallow, on a year without dry periods, in both no-tillage and conventional tillage systems. The conventional tillage provided the largest grain yield in years with dry periods.
Keywords: sequential cropping; organic fertilizers; soil management; no-tillage system; savanna